Recent developments in one-pot stepwise synthesis (OPSS) of small molecules - Xiaoming Ma; Wei Zhang (iScience, 2022)
Summary: One-pot synthesis is an active topic in organic chemistry due to its intrinsic advantages of simple operation, high mass efficiency, low cost, and less amount of waste disposal. Among three kinds of one-pot syntheses, 1) cascade reactions, 2) multicomponent reactions (MCRs), and 3) one-pot stepwise synthesis (OPSS), OPSS could be more flexible and practical since it is carried out stepwisely and have variable reaction conditions for different steps. This perspective article uses selected examples to highlight the recent development in OPSS involving cyclization, cycloaddition, rearrangement, and catalytic reactions for the synthesis of heterocyclic scaffolds, asymmetric molecules, natural products, and bioactive compounds.